Evaluation of the ability of some bacterial species isolated from UTIto form bio film - jabir, dhuha (Al-Qadisiyah Journal of Pure Science, 2022)
Urinary tract infection is one of the most serious infectious disease in the world , This study aimed to isolate and diagnose the bacteria that cause UTI and then evaluate its ability to form a biofilm. 100 urine samples were collected for a group of patients attending Al-Diwaniyah Teaching Hospital, who were confirmed to have UTI at different ages. The results showed the presence of bacteria. Escherichia coli and proteus spp in all samples(100%), while Staphylococcus aureus was found in 87% of samples , Enterobacter spp was isolated by 67% and Pseudomonas aeruginosa by 65%. Klebsiella pneumonia at 50 % and Staphylococcus epidermidis and Micrococcus spp each with 30%. Regarding the ability of the isolated bacteria to form biofilm, two methods used Congo-red agar and tube method and the results were as follows 64% for E.coli, K pneumonia with 66.6% while S. aureus showed the ability of formation with 41.6% and negative results for the rest by using tube method while Congo-red agar method results were 25% for 50% for E.coli and S. aureus. The study concluded that Congo red agar method is easy to perform and interpret, while the tube method is highly sensitive and specific.